PENGARUH TEKNIK PROYEKSI WAKTU TERHADAP PROKRASTINASI AKADEMIK SISWA DI SMK NEGERI 2 PADANG PANJANG - Windari Okral Sari; Raja Arlizon; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak : His study aims to examine the effect of time projection techniques on academic procrastination of students at SMK Negeri 2 Padang Panjang and to determine the differences in academic procrastination of students in school before and after the time projection technique. Jeneis this research is a quantitative research with an experimental method using the One-Group Pretest-Posttest Design research design. So that from these differences, can know the effect of time projection techniques on academic procrastination. The measuring instrument used in this study is the student academic procrastination measurement scale which consists of 56 items before being validated, and after validity there are 31 valid items with validity of 0.3610 and reliability of 0.882. The subject of this study amounted to 8 people selected through the results of non probability sampling techniques at SMK Negeri 2 Padang Panjang that were identified as having academic procrastination of students in the very high and high categories. Data processing that has been done can be concluded as follows: student academic procrastination before the projection technique when there are three people classified as very high and five people classified as high category. After being given the projection technique when there is a change in academic procrastination of students in one person is classified as moderate and seven people are classified as low categories. Time projection techniques have a significant positive effect on academic procrastination.Key Words : Time Projection Technique, Academic Procrastination